HALAL INDUSTRY IN INDONESIA: PROBLEM AND SOLUTION, IN MAQASHID SHARIAH PERSPECTIVE - Mu'is, Ahmad; Farida, Lailatul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
This paper aims to describe the main problem of the Halal industry, then offer suitable solutions to overcome its various problems. Literature study was used in this paper by analyzing other sources from many related journals or papers. After analyzing maqashid shariah approach, it will be taken of summary. The summary of this paper is that Indonesia is the biggest Muslim population in the world, still becoming the base of the product consumption industry rather than the producer. The Muslim role and support of many sectors to become an economic halal industry chain circle integrated are needed, such as from government, Islamic industry or Muslim business, academic experts, Muslim society, instrument information (integrated and digital) and Islamic Scholar of Indonesia (MUI). Integrative strategy, consistency and obeying of rules can make halal industry establish and progressive. Analyzed in maqashid shariah, to observe what halal industry has given good usefulness for society (maslahah mursalah).   The impact of this paper could make a positive contribution to the halal Industry and opportunity the next deep research in Indonesia. Please make just one paragraph.